Landscape-Scale Effects of Irrigation on a Dry Cereal Farmland Bird Community - Giralt, David; Pantoja, Javiera; Morales, Manuel B.; Traba, Juan; Bota, Gerard (Frontiers in Ecology and Evolution, 2021)
Landscape modification and habitat fragmentation are one of the major current threats to biodiversity. The main source of habitat fragmentation is the loss of focal habitat area, but changes in the composition of the surrounding landscape also have a direct effect on biodiversity. These changes may lead to the loss of some species but also may favor species replacement. Farmland birds in Europe are affected by landscape changes due to farmland intensification, such as the spread of irrigation, which may occur at different spatial scales. As irrigation is expected to increase in the coming years, which may affect protected areas, it is necessary to evaluate its potential consequences over focal biodiversity. In this study we assess the relationship between the increase of irrigated land at different spatial scales and changes in a dry cereal farmland bird community, bird abundance and species richness, using generalized linear models. We used a dry cereal farmland affinity index to describe the level of community specificity for dry cereal farmland. The increase in irrigated tree orchards produced an increase in species richness up to 500 m away from the irrigated area, which had a negative effect on the dry cereal farmland bird community, by triggering a replacement of specialist by generalist species. Our results show the importance of landscape-scale effects of irrigation occurring outside protected areas on the farmland bird community inside Natura 2000 sites, as well as how these effects are detected even at long distances from the disturbance source.